2009
DOI: 10.1016/j.paid.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Gray’s BIS and BAS constructs onto Factor 1 and Factor 2 of Hare’s Psychopathy Checklist – Revised

Abstract: Reinforcement Sensitivity Theory (RST; Gray, 1987; Gray & McNaughton, 2000) has proven to be a valuable tool for understanding psychopathy (e.g., Fowles, 1980, 1988; Newman & Malterer, 2009; Poythress, Edens, Landfield, Lilienfeld, Skeem, & Douglas, 2008). Recent research has linked two RST constructs, the Behavioral Inhibition System (BIS) and the Behavioral Activation System (BAS), to individuals with primary psychopathy and secondary psychopathy (Lykken, 1995; Newman, MacCoon, Vaughn, & Sadeh, 2005): Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
(60 reference statements)
1
38
0
4
Order By: Relevance
“…These three subscales form a higher-order BAS factor (13 items; Jorm et al, 1999). Recent research using the BIS/BAS scales with an inmate population has shown the scales to have good internal consistency (e.g., Wallace, Malterer, & Newman, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…These three subscales form a higher-order BAS factor (13 items; Jorm et al, 1999). Recent research using the BIS/BAS scales with an inmate population has shown the scales to have good internal consistency (e.g., Wallace, Malterer, & Newman, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The BIS inhibits appetitive responding when aversive consequences are anticipated. BIS activation results in arousal and experience of anxiety, which in turn causes inhibition of ongoing behaviors and the initiation of information processing for resolution of the conflict (Wallace, Malterer & Newman, 2009). An under-responsive BIS has been linked to disorders of disinhibition while an overresponsive BIS has been linked to internalizing disorders (Beauchaine, 2001).…”
Section: Gray's Motivational Theory Sns Activity and Motivational Tementioning
confidence: 99%
“…For instance, both Factor 1 and primary psychopathy have been associated with low scores on measures of anxiety and neuroticism, whereas Factor 2 and secondary psychopathy are associated with higher scores on these measures (Hare, 2003; Harpur et al 1989; Patrick, 1994; Ross, Benning, Patrick, et al, 2009). Both Factor 1 and primary psychopathy are associated with low scores on self-report measures (Carver & White, 1994; Caseras, Avila, & Torrubia, 2002) of BIS, whereas Factor 2 and secondary psychopathy are associated with high BAS scores (Wallace, Malterer & Newman, 2009; Ross et al, 2009). Additionally, it has been proposed that secondary psychopathy, like Factor 2, may be associated with deficits in executive control that undermine response inhibition (Hicks, Markon, Patrick, Krueger & Newman, 2004; Ross, Benning & Adams, 2007).…”
Section: Bis Functioning and The Two-factor Model Of Psychopathymentioning
confidence: 99%